2019
DOI: 10.1002/sdtp.13436
|View full text |Cite
|
Sign up to set email alerts
|

20.1: Invited Paper: Monolithic Full‐color Quantum Dot Nanoring Micro LEDs with Improved Efficiency

Abstract: Full‐color displays based on micro light‐emitting diodes (µLEDs) have gained expanding research interest. In the study, nano‐ring (NR) structures are fabricated in certain regions on a green LED epitaxial wafer, and the color of NR‐µLEDs can be tuned from green to blue duo to the strain relaxation. In order to improve the luminous efficiency of NR‐µLEDs, atomic layer deposition technique is utilized to deposit an Al2O3 layer on the sidewall of NR‐µLEDs. As a result, the photoluminescence intensity is significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Similarly, X. Ji et al demonstrated a self‐assembled QD layer grown by a Stranski‐Krastanov method that had a broadened emission bandwidth from 38 to 57 nm. [ 74 ] Recently, A. Aiello et al demonstrated a QD LED utilizing a nanowire GaN buffer layer with broadband emission and an IQE of 25%. [ 75 ] Besides the study by S. J. Chua et al, progress on QD LED has stalled, as the IQE remains below 30% even after years of development.…”
Section: Bottom‐up Growthmentioning
confidence: 99%
“…Similarly, X. Ji et al demonstrated a self‐assembled QD layer grown by a Stranski‐Krastanov method that had a broadened emission bandwidth from 38 to 57 nm. [ 74 ] Recently, A. Aiello et al demonstrated a QD LED utilizing a nanowire GaN buffer layer with broadband emission and an IQE of 25%. [ 75 ] Besides the study by S. J. Chua et al, progress on QD LED has stalled, as the IQE remains below 30% even after years of development.…”
Section: Bottom‐up Growthmentioning
confidence: 99%